Deactivation mechanism and feasible regeneration approaches for the used commercial NH3-SCR catalysts. Issue 7 (2nd April 2016) - Yu, Yanke; Meng, Xiaoran; Chen, Jinsheng; Yin, Liqian; Qiu, Tianxue; He, Chi
ABSTRACT: The deactivation and regeneration of selective catalytic reduction catalysts which have been used for about 37, 000 h in a coal power plant are studied. The formation of Al2 (SO4 )3, surface deposition of K, Mg and Ca are primary reasons for the deactivation of the studied Selective catalytic reduction catalysts. Other factors such as activated V valence alteration also contribute to the deactivation. Reactivation of used catalysts via environment-friendly and finance-feasibly approaches, that is, dilute acid or alkali solution washing, would be of great interest. Three regeneration pathways were studied in the present work, and dilute nitric acid or sodium hydroxide solution could remove most of the contaminants over the catalyst surface and partly recover the catalytic performance. Notably, the acid–alkali combination washing, namely, catalysts treated by dilute sodium hydroxide and nitric acid solutions orderly, was much more effective than single washing approach in recovering the activity, and NO conversion increased from 23.6% to 89.5% at 380°C. The higher removal efficiency of contaminants, the lower dissolution of activated V, and promoting the formation of polymeric vanadate should be the main reason for recovery of the activity.